A new species, Poecilocampa deqina (Lepidoptera: Lasiocampidae), from China - Saldaitis, Aidas; Pekarsky, Oleg (Zootaxa, 2015)
A new lappet moth, Poecilocampa deqina sp. n., from southwest China is described. Previously the genus Poecilocampa Stephens included three species (Poecilocampa tenera O. Bang-Haas, 1927, Poecilocampa nilsinjaevi Zolotuhin, 2005 and Poecilocampa morandinii Zolotuhin & Saldaitis, 2010) from China territory. The new species differs in appearance, genitalia and DNA from its closest congener, P. morandinii.